The effects of different intermittent fasting regimens in people with type 2 diabetes: a network meta-analysis - Xiaoyu, Wen; Yuxin, Xiao; Li, Lai (Frontiers in Nutrition, 2024)
Objective: To compare the effects of four intermittent fasting regimens on blood glucose and insulin sensitivity in people with type 2 diabetes.Methods: Randomized controlled trials of intermittent fasting in the treatment of patients with type 2 diabetes mellitus in PubMed, the Cochrane Library, Embase, ScienceDirect, Web of Science, CNKI, VIP Database, and WANFANG Database were searched for from the library to September 2023. 2 review authors independently screened studies and extracted data. RevMan 5.4 was used for direct comparison of meta-results. Network meta-analysis was performed using Stata16 software.Results: 13 studies with a total of 867 patients were included. The intervention effects of twice-per-week fasting, fasting-mimicking diet, time-restricted eating, and peridic fasting were better than that of conventional diet. The results of the network comparison showed that there was no significant difference in the intervention effect of the intermittent fasting regimens. SUCRA ranking results showed that the twiceper-week fasting was best for comprehensive interventions for improvement.From the perspective of fasting blood glucose, glycated hemoglobin and insulin resistance,the twice-per-week fasting intervention has a good effect, which can be used as a reference for patients with inter-type 2 diabetes to choose intermittent fasting regimen. However, more clinical trials are needed to verify this at a later stage.